The Role of AI in Shaping the Future of the Gig Economy: A Study of Gig Workers in Urban India - Dawle, Abhijeet; Mishra, Pradeep Kumar; Dapkekar , Amol; Waychal , Sanjay; Sharma, Jitendra (International Journal of Social Sciences and Management, 2025)
This study examines the disruptive nature of AI-powered platforms that change job distribution, pay, and skill growth for gig workers over time. Reading research on AI from reports by international organizations such as the International Labour Organization (ILO) and the World Economic Forum, together with white papers on major gig platforms, indicates the double-sided nature of AI in parallel. On the one hand, AI boosts operational excellence and opens room for skill development & inclusive employment. However, this leads to new problems such as algorithmic bias, fluctuations in income, and less worker autonomy. This research further investigates how AI can be instrumental in bridging skill imbalances to promote economic inclusion, especially in less advantaged groups. Important policy recommendations include fully algorithm-transparent initiatives, the introduction of social protection access, and the provision of skill enhancement in the form of skill development plans. It also highlights the regional inequality solution in the gig economy in India through artificial intelligence, which can be a way to address both, the urban and the rural employment gap. With the rapid expansion of the gig economy, this research offers valuable findings for policymakers, platform developers, and gig workers regarding the need for a balance between efficiency fairness, and equity. This study confirms the importance of deploying AI responsibly to enable sustainable development, economic resilience, and social inclusivity in a dynamic labor market. Int. J. Soc. Sc. Manage. Vol. 12, Issue-3: 150-157.